Recent advances in non‐thermal and thermal processing of jackfruit (Artocarpus heterophyllus Lam): An updated review. Issue 9 (16th May 2022) - Nelluri, Puja; Venkatesh, Thulasiraman; Kothakota, Anjineyulu; Pandiselvam, Ravi; Garg, Ramandeep; Eswaran, Vishnu; Vaddevolu, Uday Bhanu Prakash; Venkatesh, Rangaswamy; Mousavi Khaneghah, Amin
Abstract: Jackfruit ( Artocarpus Heterophyllus Lam .) is an underexploited seasonal fruit that is rich in vitamins, minerals, proteins, and carbohydrates. Its commercialization and storage are limited due to its highly perishable nature. At the same time, operations such as peeling, cutting, and coring operations are difficult to perform manually. This review sums up the recent development in the area of novel thermal and nonthermal processing techniques such as retort pouch processing, microwave processing, irradiation, high‐pressure processing (HPP), pulsed electric field technology, ultrasound, supercritical fluid extraction, cold freezing, hurdle technology, and minimal processing were discussed to preserve and processed jackfruit. The impact of different processing techniques on jackfruit's quality, sensory characteristics, and storage period was also demonstrated. Industrial challenges and their prospects are also explicated for entrepreneur beneficiaries. Thermal methods resulted in a more significant loss of nutrients than nonthermal methods. For better results, pooled heat treatment with nonthermal methods is effective. Ultrasonication significantly improved the quality of thermal techniques, micro‐wave treatment, and nonthermal methods. Novelty impact statement: Use of novel thermal and nonthermal methods for jackfruit processing is suggested. Combination of mild heat with nonthermal methods was more effective for jackfruit preservation. Microwave and ultrasonication are most effectively analyzed for jackfruit processing. Industrial challenges and their prospects are also explicated for entrepreneur beneficiaries.